Assessing the Relationship between Neurocognitive Performance and Brain Volume in Chronic Moderate-Severe Traumatic Brain Injury - Konstantinou, Nikos; Pettemeridou, Eva; Seimenis, Ioannis; Eracleous, Eleni; Papacostas, Savvas S.; Papanicolaou, Andrew C; Constantinidou, Fofi (My University, 2016)
Characterize the scale and pattern of long-term atrophy in gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF) in chronic moderate-severe traumatic brain injury (TBI) and its relationship to neurocognitive outcomes.
Keywords: Brain atrophy; Grey matter; Neurocognitive/neuropsychological assessment; TBI; VBM; White matter